Care in pediatric oncology: a cross-sectional analysis of the quality of life of nursing professionals - Raíssa Silva Souza; Fernanda Lopes de Araújo; Bruna Figueiredo Manzo; Juliana de Oliveira Marcatto; Lívia Cozer Montenegro; Paulo Roberto Mendonça Silva; Delma Aurélia da Silva Simão (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to assess and correlate sociodemographic and work variables with the quality of life (QoL) of nursing professionals who work with children and adolescents with cancer. Methods: a cross-sectional, analytical, correlational study with 123 volunteers from a public hospital. Sociodemographic characterization questionnaire and WHOQOL-Bref have been used. Results: "sex" (p=0.017), "work shift" (p=0.022), "employment relationship" (p=0.049) "having children" (p=0.002), "work sector" (p=0.047), "work shift" (p=0.007) and "employment relationship" (p=0.040) had worse quality of life. "Job duty length" (p=0.027) and "years of study" (p=0.001) and, conversely, "age" (p=0.004) and "job tenure" (p=0.001) were positively correlated with quality of life domains. Conclusions: most professionals rated the overall quality of life as "good". Sociodemographic and work characteristics are associated with worse quality of life. The more years of study and the better job duty length the better the quality of life.